Optimizing the energy efficiency of vessels using recovery boilers. Issue 1 (September 2020) - Faităr, C; Nedelcu, A; Buzbuchi, N; Stan, L; Dumitrache, C
Abstract: In general, the energy requirement on board the ship is divided into three categories: propulsion power, auxiliary electric power and auxiliary thermal power. The WHRS system uses the energy dissipated from the exhaust gases, but also it can be used the energy from the main engine cooling water system (high temperature freshwater cooling circuit) and the air system by applying a WHR heat exchanger element to the main engine. The application of CFD in the analysis of heat exchangers is somewhat limited, being able to be used in the initial dimensioning thus reducing the number of prototypes and offering a clear image of the phenomena of heat transport from the equipment. In the economizer the water supply will turn into steam, so the problem to be solved is the two-phase flow with two different properties and the phase transformation of water from liquid to steam. These two phases are mixed in the economizer tubes at the macroscopic level. The two phases can coexist in dispersed form, droplets or steam bubbles. In the fluid field can coexist phases with different densities or different speeds.